Governance as a foundation of country competitiveness: A cross-country study - Diyah Novitasari (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2026)
A country's global competitiveness is shaped by its institutional and governance framework. This study examines how key governance dimensions—government effectiveness, political stability and absence of violence/terrorism, and voice and accountability— influence national competitiveness with infrastructure and economic performance as controlled variables. Using a cross-country quantitative approach, the study analyzes data from 69 countries in the World Competitiveness Ranking 2025 and the Worldwide Governance Indicators 2023. A multiple linear regression model shows strong explanatory power, with an R-squared of 0.9268. Results reveal that government effectiveness has the strongest positive and significant impact on competitiveness, followed by infrastructure and economic performance. Unexpectedly, both political stability and voice and accountability have significant negative relationships with competitiveness. This suggests that an extreme, possibly authoritarian stability and excessive accountability may hinder flexibility and efficient decision-making. Ultimately, enhancing competitiveness requires deep bureaucratic and institutional reforms to boost government effectiveness. It also calls for balancing political order, public participation, and agile, evidence-based policymaking